Sport in the Context of Social Sciences. 2012. Eds. W. J. Cynarski, J. Kosiewicz, K. Obodyński - Mazurkiewicz, Michał (Respectus Philologicus, 2013)
Sport in the Context of Social Sciences. W. J. Cynarski, J. Kosiewicz, K. Obodyński, Eds. 2012. Rzeszów: Wydawnictwo Uniwersytetu Rzeszowskiego. 282 pp. ISBN 978-83-7338-813-0.Sport has been a very important component of human existence for ages. It is a complex and colourful phenomenon which arouses the intense interest of fans all over the world and which can be analysed from different points of view. Sport is definitely something more than pure entertainment. Anyone interested in sport should become familiar with the latest fruit of the work of the Polish scientists conducting research on different aspects of sports history and sociology. It is worth emphasizing that in Poland there are numerous scholars who have put sport at the centre of their scientific interests.